The Effect Of Light Emitting Diodes Intensity To Germination And Growth Of Plant - Mohammad Nurmustaqim Bin Abdul Rahman - Mohammad Nurmustaqim Bin Abdul Rahman (2023)
A study on the effect of light-emitting diodes (LEDs) intensity to the germination and growth of plant has been conducted.White and green beans were grown under red and white LEDs with different level of light intensities.